2008
DOI: 10.1152/ajpheart.01051.2007
|View full text |Cite
|
Sign up to set email alerts
|

A profound decrease in maternal arginine uptake provokes endothelial nitration in the pregnant rat

Abstract: While a specific role for nitric oxide (NO) in inducing the hemodynamic alterations of pregnancy is somewhat controversial, it is widely accepted that excess NO is generated during pregnancy. L-Arginine is the sole precursor for NO biosynthesis. Among several transporters that mediate L-arginine uptake, cationic amino acid transporter-1 (CAT-1) acts as the specific arginine transporter for endothelial NO synthase. The present study was designed to test the hypothesis that, during pregnancy, when arginine consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
(45 reference statements)
1
25
1
Order By: Relevance
“…Several studies demonstrated down-regulation of CAT-1 activity by PKC (5,6,44,45). These studies suggested that CAT-1 phosphorylation affects its functional properties.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies demonstrated down-regulation of CAT-1 activity by PKC (5,6,44,45). These studies suggested that CAT-1 phosphorylation affects its functional properties.…”
Section: Discussionmentioning
confidence: 96%
“…A possible involvement of PKCα in the regulation of L -arginine transport in different cell types has been discussed for the last several years [23,24]. We have recently reported in 4 different experimental models characterized by diminished arginine transport, namely, hypercholesterolemia, chronic renal failure, pregnancy, and aging in the male rat, a post-translational regulation of CAT-1 which was associated with upregulation of PKCα [15,16,18,25]. We have decided to focus exclusively on the membrane fraction of PKCα since this is where the interaction between PKCα and CAT-1 occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of radiolabeled L -arginine in the rat aorta was measured according to previously described methods [16]. Immediately after sacrifice, the aorta was carefully excised from the left renal artery to the aortic valve ring and placed in ice-cold HEPES.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has come to light that maternal aortic L-arginine uptake is profoundly attenuated in pregnancy, and the researchers of that study assume that rather than supplying its own endothelium, maternal L-arginine stores are depleted due to a preferential shift to the fetus. 39 These data could explain the reduction in L-arginine transport in platelets from pregnant hypertensive rats. Both influx and availability of intracellular L-arginine are limiting factors in NO production.…”
Section: Discussionmentioning
confidence: 90%